[Smallest addition to the British Empire] - (:unkn) unknown (Stephens Ltd., Trinidad, 2011)
The postcard shows a small island which appeared on the 3rd November 1911 off the island of Trinidad. The island would have fallen under the jurisdiction of the British Empire because at that time Trinidad was a colony of the British Empire until the country's independence in 1962.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Volcanic eruptions; Islands